POLA RETAK LENTUR GESER BALOK BETON BERTULANG DENGAN ORTHOTROPIC MODEL - S.T., M.T., DEDI BUDI SETIAWAN (Politeknik Negeri Semarang, 2016)
Test the load to collapse needed to test the reliability of the structure , ie by knowing the maximum load that can be borne by the structure. The process of bending and deflection of reinforced concrete beams is also necessary for students to understand the world of construction and reinforcement due to shear or bending , through experimental studies and numerical studies. Whereas laboratory tests conducted on relatively more expensive. One solution to the numerical methods are finite element methode. The main purpose of this research is to create a simulation of bending, deflection, maximum load and cracking for reinforced concrete beam with orthotropic models. So the simulation of bending, deflection, maximum load and cracks can be represented with this program without always perform laboratory testing. Program performance is analyzed based on laboratory test results and literature. The pattern of cracked beam bending shear formed shows the influence of concentrated loads are in the area moment of pure, cracks formed experiencing slope indicating still have a shear work but further away from the location of concentrated load slope becomes increasingly erect indicating less influence concentrated load , While near the pedestal cracks experiencing tilt direction marks in those areas experiencing the combined effects of shear stress and maximum normal stresses are close to zero and the impact of support reaction. The pattern of cracked beam bending pure looks toward the crack perpendicular to the horizontal axis beam this is due to the absence of shear stress working along the span structure, in the absence of shear strain, the strain off the main drag parallel to the horizontal axis and direction cracked up to be perpendicular direction tensile strain, this corresponds to the existing reference.Kata kunci : finite element, reinforced concrete beams, crack pattern.